Segurança da informação: banco de dados dos servidores do sindicato dos trabalhadores das instituições federais de ensino superior no estado do Pará - CORRÊA, Renan Cândido Vales (2018)
In this conjecture the general objective of this study is to present the means of security of the information of the database of the Trade Union of Workers of the Federal University of Pará of the workers of the Federal Institutions of Higher Education in the State of Pará. The specific objectives are: to verify what the types of security in the hardware supports and software are offered in the database of the union; identify which means of information security the database system offers; identify if there has already been any loss of information in the database due to a security breach in the system. The methodology used focused on the bibliographic research on the subject based on a review of the authors who approach the subject, who understand information security and database. For this, a bibliographical research was done in the database area, an interview and a questionnaire with those in charge of the syndicate database. It is concluded that the information security in the analyzed database, is satisfactory, of course, always not forgetting that in the database environment, nothing is 100% safe, but with the right tools, data loss damages are children.